2014
DOI: 10.1007/s40593-014-0031-y
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Overcome Cultural Conflict through Engaging with Intelligent Agents in Synthetic Cultures

Abstract: Providing opportunities for children to engage with intercultural learning has frequently focused on exposure to the ritual, celebrations and festivals of cultures, with the view that such experiences will result in greater acceptance of cultural differences. Intercultural conflict is often avoided, bringing as it does particular pedagogical, ethical and political dilemmas of which cultures we place in conflict in the multicultural classroom. In this paper we discuss an alternative approach, providing children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 27 publications
(15 reference statements)
0
9
0
Order By: Relevance
“…Over 130 children were engaged in the MIXER summative evaluation, with the results presented in [13]. In this paper our focus is not the evaluation of the evaluand per se, but rather on whether we had managed to have an impact on stage-4 of the optimal response model.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over 130 children were engaged in the MIXER summative evaluation, with the results presented in [13]. In this paper our focus is not the evaluation of the evaluand per se, but rather on whether we had managed to have an impact on stage-4 of the optimal response model.…”
Section: Resultsmentioning
confidence: 99%
“…It developed MIXER [13], an interactive narrative or Serious Game, aiming to support 9-11 year old children in learning how to recognize and resolve cultural differences. MIXER provides the evaluand for the studies reported in this paper with eCute's evaluation approach involving multiple formative evaluations feeding into the design of MIXER throughout the lifecycle.…”
Section: Evaluand and Evaluation Contextmentioning
confidence: 99%
“…The study of cultural communication has gained popularity over the last decade and many researchers have developed virtual simulation systems to represent different cultural behaviours and communication. These systems are designed to provide learners with an understanding of different cultural behaviours through complex models of a virtual agent's behaviour (Degens, Endrass, Hofstede, Beulens, & André, 2014;Endrass et al, 2011;Hall et al, 2015;Kistler, Endrass, Damian, Dang, & André, 2012;Mascarenhas et al, 2013), useful scenarios (Endrass et al, 2011;Hall et al, 2015;Kistler et al, 2012;Mascarenhas et al, 2013), or powerful interactive tools (Kistler et al, 2012;Mascarenhas et al, 2013). The learners observe the situation from a third-person point of view (POV), just as they are looking at other behaviours as examples (Degens et al, 2014;Hall et al, 2015;Kistler et al, 2012), and then they are asked to interact with the agent first-person POV (Hall et al, 2015;Mascarenhas et al, 2013) same as in the real world.…”
Section: Related Workmentioning
confidence: 99%
“…Popular formal models of national cultures, such as the dimensional models of Hofstede et al (2010) and Hall (1966), might appear to offer promise as a basis for modelling culture in culturally-aware educational technologies. However, the authors of this article did not find them to live up to this potential; as Hall et al (2014) note, "The Hofstede dimensions are zoomed-out abstractions, derived from aggregated society-wide analysis." It is difficult to take these general cultural characteristics and apply them to specific design problems, such as how to support help-seeking behavior across cultures.…”
mentioning
confidence: 92%
“…The final paper, by an interdisciplinary multinational European team (Hall et al 2014), is also in the area of cultural instruction. It describes an experiential learning environment in which children learn cultural conflict competence by exploring the interactions between virtual agents representing synthetic cultures.…”
mentioning
confidence: 99%